أكوام الحجارة المقدسة "الكركور نموذجا" - عباس, رضوان (Changement Social, 2018)
The presentpaperhighlights the phenomenon of pilingprecious stones, thatreligiousspacewhich carries thoserituals and beliefsassociated to a sort of sacredspacesrestrictedwithin a givenspace. It is the “Gorgoor”, whichmeans “the religioussacredspace”, made up fromdifferent stone piles which are in fact stones extractedfromfields  to facilitateitsplowing and thenitsgathering in piles. It sometimesdoes not exceedsomesigns and if twoindividualswant to confirm to eachothertheir passage to a given place theyjust have to put a small “Gargoor” …to show his passage there